The Path of Marketing Channel Development to China’s Market for Bang Bo Plaslid Products, Samut Prakan Province - Chanachaiphuwapat, Sarunthita; Bamrungpanit, Sukrittawat; Ruenyat, Wimolmamee (Area Based Development Research Journal, 2020)
For non-domestic products, China prefers imported products from Thailand and the neighboring countries because of products standards and reliability. As Chinese people living in Yunnan province have a high tendency in consuming crispy processed fish, it is opportunistic for Thailand’s processed ready-to-eat Plaslid products and attain market share in China. The objectives of this research are 1) to develop the packaging and brand image for Bang Bo Plaslid, and 2) to create alliance and trade partners at Jinghong, Yunnan province. This research employs the action research approach with participatory communication conducted with the 5 potential entrepreneurs, namely, Mae Amneuy, Sansomboon, Mae Nittaya, Slit-Slid and Aei-Tee. The process of activities consists of knowledge training, business analysis, production standards preparing, packaging and brand image development, business matching and provisional export trading. The activities take place in two geographical areas – Bang Bo at Samut Prakan province for the production and Mae Sai in Chiangrai province for trading channel and transportation. The findings show entrepreneurs’ understanding of export standards and preparation process as well as opportunities to do business with China. Their products have suitable packaging for export, well-represented brand image, and advertising media that links to Plaslid’s identity. The entrepreneurs’ cooperation under the name “The processed Plaslid entrepreneurs of Bang Bo - Lanna” brings strength and credibility to a broader public. Finally, establishing connection with alliance and trade partners in Chiang Rai province of Thailand opens up a trading channel to China and projected to increase 10 % of total sales of all products.